1999
DOI: 10.1042/cs19980356
|View full text |Cite
|
Sign up to set email alerts
|

Altered cardiovascular haemodynamics and baroreceptor‒heart rate reflex in adult sheep after prenatal exposure to dexamethasone

Abstract: Numerous epidemiological studies, together with mounting evidence from studies in animals, point to a correlation between an adverse intrauterine environment and the early onset of cardiovascular and metabolic diseases later in life. We were the first to show that sheep exposed to dexamethasone (0.28 mg.kg-1.day-1 for only 2 days) at the end of the first month of pregnancy (PTG1), but not those exposed at the end of the second month of pregnancy (PTG2), had a higher basal mean arterial pressure (MAP) 19 months… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
2

Year Published

2005
2005
2014
2014

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 17 publications
2
28
2
Order By: Relevance
“…Steroids may lead to microvascular dysfunction by altering vascular responses to vasoconstrictors, including induction of endothelin vasoconstriction and attenuating endothelium-dependent vasorelaxation [34,35]. A central mechanism has been proposed with alteration of baroreceptor centres in the brainstem [36]. However, despite these findings, Dalziel et al found no increased risk of hypertension in their 30-year follow-up after antenatal exposure to betamethasone [37].…”
Section: Discussionmentioning
confidence: 95%
“…Steroids may lead to microvascular dysfunction by altering vascular responses to vasoconstrictors, including induction of endothelin vasoconstriction and attenuating endothelium-dependent vasorelaxation [34,35]. A central mechanism has been proposed with alteration of baroreceptor centres in the brainstem [36]. However, despite these findings, Dalziel et al found no increased risk of hypertension in their 30-year follow-up after antenatal exposure to betamethasone [37].…”
Section: Discussionmentioning
confidence: 95%
“…Both produce hypertension in the adult sheep offspring (Dodic et al 1998(Dodic et al , 2002b and both produce a decrease in nephron number after nephrogenesis is completed (Wintour et al 2003a,b;Moritz et al 2004). However, as shown in (Dodic et al 1999), whereas that attributable to cortisol is dependent upon increased peripheral resistance (McAlinden et al 2004). In addition, the long-term changes in gene expression in various sections of the brain also differ (Fig.…”
Section: Introductionmentioning
confidence: 93%
“…When dexamethasone or cortisol is infused early into the ewe (from 26-28 days of gestation; term is 145-150 days), all offspring are hypertensive from 3-5 months (Dodic et al 1998(Dodic et al , 2002aRoghair et al 2005). In the case of dexamethasone treatment, the hypertension is associated with an increased cardiac output and no change in peripheral sensitivity to infused angiotensin II (Dodic et al 1998(Dodic et al , 1999Roghair et al 2005). The in vitro responsiveness of mesenteric arteries of hypertensive offspring is actually less responsive to angiotensin II, whereas the coronary arteries show increased vasoconstriction to ang II and other second-messenger-dependent vasoconstrictors (Dodic et al 1998;Roghair et al 2005).…”
Section: Introductionmentioning
confidence: 96%
“…Short-term infusions of glucocorticoids during early-or midgestation culminate in hypertension in both sheep (Dodic et al 2002) and rat offspring respectively (Ortiz et al 2003, Singh et al 2007a. Interestingly, the outcome is highly dependent upon the timing of exposure as the same level of glucocorticoid exposure did not result in hypertension when administered at other stages of development (Dodic et al 1999, Ortiz et al 2003. Models of uteroplacental insufficiency have been developed to explore the long-term effects of reduced placental function in late gestation in the rat, which coincides with the period of rapid fetal growth.…”
Section: Perturbations Resulting In Developmental Programing: the Impmentioning
confidence: 98%